Tactical Asset Management or Financial Trauma?: Why the Abandonment of Buy-and-Hold May be a Symptom of Posttraumatic Stress - Bradley Klontz; Sonya L Britt (Journal of Financial Therapy, 2012)
The purpose of this study was to measure the psychological impact of the 2008 financial crisis on financial planners. Recent surveys of financial advisors have confirmed a fundamental shift away from strategic management in favor of tactical management, with planners reporting having had made on average 2.15 adjustments in the past 12 months to take advantage of market changes (FPA 2012 Trends in Investing Study, 2012), and 83% of financial planners planning to make at least one tactical adjustment within the next three months (Veres, 2012). This article explores the psychological impact of the 2008 financial crisis on financial planners, measuring symptoms of posttraumatic stress and related changes in belief systems as a result of the crisis. In the months following the 2008 crisis, 93% of the planners surveyed reported medium to high levels of posttraumatic stress. We hypothesize that while the acute psychological distress has diminished the cognitive changes have persisted and may ultimately put the financial health of clients at risk.
Keywords: Financial therapy; financial planning; posttraumatic stress; tactical asset management; financial trauma